Predicting Membrane Protein Types Based on Fusing Information Feature and Ensemble Machine Learning Model - He, Ping-an; Chen, Shuyue; Su, Pengcheng; Dai, Qi (Current Proteomics, 2024)
BackgroundMembrane proteins participate in many physiological and biochemical functions essential for cellular function. Identifying membrane protein types is a critical task in biology for studying the tertiary structure of membrane proteins.MethodsIn this paper, a novel classification method is proposed to predict membrane protein types based on the ensemble learning model, fusing protein sequence features and secondary structure information.ResultsThe performance for predicting the type of membrane proteins was improved compared with other machine learning models.ConclusionUtilizing multimodal features and machine learning methods can effectively predict and classify membrane protein types.
Keywords: Membrane proteins